A Situational Analysis and an Action Strategy for theCircular Economy in the Textile Industry - Pérez-Canto, Salvador; Doblas-Florido, Maria Angeles (Wiley, 2025)
This study examines the transition from the traditional Linear Economy to the Circular Economy model, focusing on the Spanish textile industry. Given the sector's significant environmental impact, characterized by pollution, excessive water consumption, high waste generation, and the use of harmful materials, circularity emerges as a crucial strategy for fostering sustainability and resilience. Through a survey administered to a panel of experts, including industry managers, academics, policymakers, and practitioners, this research explores the sector's circular practices, key challenges, and future expectations. The collected data is analyzed using Principal Component Analysis to identify critical factors influencing the transition. Findings highlight the urgent need to shift away from the linear production model to minimize resource consumption and environmental impact. Based on these insights, the originality of this study lies in its proposed action strategy to advance circularity in the textile industry, which is intended to promote sustainable production, improve profitability, and enhance both customer and societal satisfaction.
Keywords: Industria textil; Economía circular; Desarrollo sotenible; circular economy; principal component analysis; sustainability; sustainable development goals; textile industry